2018
DOI: 10.14814/phy2.13548
|View full text |Cite
|
Sign up to set email alerts
|

The impact of a short-term high-fat diet on mitochondrial respiration, reactive oxygen species production, and dynamics in oxidative and glycolytic skeletal muscles of young rats

Abstract: Multiple aspects of mitochondrial function and dynamics remain poorly studied in the skeletal muscle of pediatric models in response to a short-term high-fat diet (HFD). This study investigated the impact of a short-term HFD on mitochondrial function and dynamics in the oxidative soleus (SOL) and glycolytic extensor digitorum longus (EDL) muscles in young rats. Young male Wistar rats were submitted to either HFD or normal chow (NCD) diets for 14 days. Permeabilized myofibers from SOL and EDL were prepared to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

8
20
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(30 citation statements)
references
References 35 publications
(99 reference statements)
8
20
2
Order By: Relevance
“…The overexpression of PGC1α also promoted a fiber-type switch from a glycolytic toward a more oxidative phenotype in mice ( Lin et al, 2002 ). In line with our previous work ( Leduc-Gaudet et al, 2018 ), we could not observe any difference in the expression of PGC1α, suggesting that mitochondrial biogenesis is not altered in SOL or EDL muscles in response to our short-term HFD. Overexpression of PPARγ was also observed in the SOL muscle.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The overexpression of PGC1α also promoted a fiber-type switch from a glycolytic toward a more oxidative phenotype in mice ( Lin et al, 2002 ). In line with our previous work ( Leduc-Gaudet et al, 2018 ), we could not observe any difference in the expression of PGC1α, suggesting that mitochondrial biogenesis is not altered in SOL or EDL muscles in response to our short-term HFD. Overexpression of PPARγ was also observed in the SOL muscle.…”
Section: Discussionsupporting
confidence: 93%
“…Our results show that larger LDs were observed in SOL, but not in EDL muscles; these discrepancies could be explained by differences in the experimental model, namely by the age and the species tested. Further, we have recently reported that 14 days of HFD significantly increase palmitic acid utilization while altering the expression of genes involved in the regulation of mitochondrial dynamics in both oxidative and glycolytic muscles of young rats ( Leduc-Gaudet et al, 2018 ). Interestingly our results obtained with the same model show a decline in ambulatory activity in response to the short-term HFD ( Andrich et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…Mitochondrial respiratory function was increased in both the soleus and gastrocnemius with HFD. This is in contrast to our hypothesis, but some studies have also reported an increase in mitochondrial function with HFD [14,15,39]. While two studies have observed a decrease in mitochondrial respiratory function with HFD [11,12].…”
Section: Discussionsupporting
(Expert classified)
“…We also observed that subjecting mice to an HFD did not alter mitochondrial bioenergetics. This could be due to subjecting our mice to a short-term high fat feeding regiment, which has previously been shown to have little impact on mitochondrial bioenergetics (19). We also observed that mitochondria from GRX2 heterozygotes contained higher PDH levels, which could also account for the increase in muscle fuel metabolism.…”
Section: Discussionmentioning
confidence: 75%